PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KOMISARIS INDEPENDEN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN - Syam, Firlin; Martha, Lidya (Ensiklopedia of Journal, 2025)
Abstract: This research aims to analyze the influence of Corporate Social Responsibility (CSR) and Independent Board of Commissioners on profitability in banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023.The research method used is quantitative with panel data. The research sample was selected using the purposive sampling method, resulting in 9 banking companies that met the criteria. Profitability is measured by Return On Asset (ROA), CSR is measured by the Global Reporting Initiative (GRI), and the Independent Board of Commissioners is measured by the proportion of independent commissioners in the board of commissioners. The research results show that CSR does not have a significant impact on profitability, whereas the Independent Board of Commissioners has a positive and significant impact on profitability. In conclusion, CSR disclosure has not yet provided a direct benefit to profitability, while the presence of an effective independent board of commissioners can enhance the profitability of banking companies.Keywords: Corporate Social Responsibility, Independent Commissioners, Profitability, Banking, Panel Data